Implementation of the integrated work system in the secondary manufacturing department of British American Tobacco Bangladesh - Sakib, Shadman (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.